2014
DOI: 10.1139/bcb-2014-0066
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between 2 extracellular loops influences the activity of the cystic fibrosis transmembrane conductance regulator chloride channel

Abstract: Activity of the cystic fibrosis transmembrane conductance regulator (CFTR) chloride channel is thought to be controlled by cytoplasmic factors. However, recent evidence has shown that overall channel activity is also influenced by extracellular anions that interact directly with the extracellular loops (ECLs) of the CFTR protein. Very little is known about the structure of the ECLs or how substances interacting with these ECLs might affect CFTR function. We used patch-clamp recording to investigate the accessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Interestingly, a recent study by Cui et al [ 13 ] has shown that three charged amino acid residues in ECL1 (D110, E116 and R117) are involved in stabilising the architecture of the outer pore of CFTR by interacting with other charged residues, including K892 in ECL4. Furthermore, our lab has recently demonstrated, through cross-linking of residues in ECL1 and ECL4, that the relative movement of these two ECLs is necessary for normal channel gating [ 10 ] which further demonstrates the important role of the ECLs in CFTR channel function.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study by Cui et al [ 13 ] has shown that three charged amino acid residues in ECL1 (D110, E116 and R117) are involved in stabilising the architecture of the outer pore of CFTR by interacting with other charged residues, including K892 in ECL4. Furthermore, our lab has recently demonstrated, through cross-linking of residues in ECL1 and ECL4, that the relative movement of these two ECLs is necessary for normal channel gating [ 10 ] which further demonstrates the important role of the ECLs in CFTR channel function.…”
Section: Discussionmentioning
confidence: 99%
“…These mutations affect the stability of the CFTR ion pore, resulting in reduced conductance of CFTR (34,42). Q890X and K892C mutations in ECL4 have been reported to affect channel gating and extracellular anion interaction (10,29,42). ECL4 is the only extracellular loop that contains Nlinked glycosylation sites (N894 and N900) (10).…”
Section: Domainsmentioning
confidence: 99%
“…Q890X and K892C mutations in ECL4 have been reported to affect channel gating and extracellular anion interaction (10,29,42). ECL4 is the only extracellular loop that contains Nlinked glycosylation sites (N894 and N900) (10). Many studies have been performed on the function of CFTR's intracytoplasmic loops (ICLs) including their roles in regulating inter-molecular interactions as well as CFTR interactions with other proteins.…”
Section: Domainsmentioning
confidence: 99%